2022
DOI: 10.1021/jacs.2c05726
|View full text |Cite
|
Sign up to set email alerts
|

DNA Strand Displacement Driven by Host–Guest Interactions

Abstract: Base-pair-driven toehold-mediated strand displacement (BP-TMSD) is a fundamental concept employed for constructing DNA machines and networks with a gamut of applications�from theranostics to computational devices. To broaden the toolbox of dynamic DNA chemistry, herein, we introduce a synthetic surrogate termed host−guest-driven toeholdmediated strand displacement (HG-TMSD) that utilizes bioorthogonal, cucurbit[7]uril (CB[7]) interactions with guest-linked input sequences. Since control of the strand-displacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…Finally, Jayawickramarajah and co-workers used the CB [7] •ADA host−guest pair as a surrogate to replace the regularly used base pair for DNA strand displacement, modulating enzyme activity and layered reactions detecting specific microRNA. 91 This method is a positive alternative to the traditional base-pair-driven, toehold-mediated strand displacement, enhancing the diversity of the toolbox for the manipulation of the function of dynamic DNA machines. Recently, Wang and co-workers employed supramolecular systems based on hyaluronic acid (HA)-modified CB [7] (CB [7]-HA, Figure 15) and TPP-PEG-ADA (TPP: triphenylphosphonium, a well-known moiety targeting mitochondria) 92 to get some control on the biological properties of mitochondria (Figure 16).…”
Section: F-cb[7]s In Molecular and Cell Biologymentioning
confidence: 99%
“…Finally, Jayawickramarajah and co-workers used the CB [7] •ADA host−guest pair as a surrogate to replace the regularly used base pair for DNA strand displacement, modulating enzyme activity and layered reactions detecting specific microRNA. 91 This method is a positive alternative to the traditional base-pair-driven, toehold-mediated strand displacement, enhancing the diversity of the toolbox for the manipulation of the function of dynamic DNA machines. Recently, Wang and co-workers employed supramolecular systems based on hyaluronic acid (HA)-modified CB [7] (CB [7]-HA, Figure 15) and TPP-PEG-ADA (TPP: triphenylphosphonium, a well-known moiety targeting mitochondria) 92 to get some control on the biological properties of mitochondria (Figure 16).…”
Section: F-cb[7]s In Molecular and Cell Biologymentioning
confidence: 99%
“…It can also provide a reaction chamber by maintaining space proximity between two individual molecules, and give information about reaction kinetics. [127][128][129][130] By this means, Yuan et al showed that single-molecule junctions formed in an STM-BJ setup could provide a testbed to detect temporal signals from reactants in ultra-low concentrations, which are invisible to methods such as mass spectroscopy. 131 They used hostguest assembly to study the conductance change during complexation of 1,2-bis(4-pyridinyl)ethylene (BPE) monomer and CB [8], and finally the dimerization product to BPE2@CB [8] upon UV irradiation.…”
Section: Host-guest Interactionmentioning
confidence: 99%
“…The DNA strand displacement reaction (SDR) is a procedure whereby DNA strands undergo structural changes based on binding force differences for exporting new dsDNA. , If the SDR is performed repeatedly, it can constitute a circular DNA SDR (CD-SDR). , CD-SDR is an entropy-initiated self-assembly reaction that offers the merits of dynamics, manipulability, high controllability, and mild reaction conditions, opening the door to the design of novel sensing strategies. Therefore, the present study envisages the use of the target as a primer to complete trace detection of the target by means of the signal accumulation of CD-SDR.…”
Section: Introductionmentioning
confidence: 99%